Green and Red Brazilian Propolis: Antimicrobial Potential and Anti‐Virulence against ATCC and Clinically Isolated Multidrug‐Resistant Bacteria. Issue 8 (22nd June 2021) - de Souza Silva, Thayná; Silva, Júlia M. B.; Braun, Gláucia H.; Mejia, Jennyfer A. A.; Ccapatinta, Gari V. C.; Santos, Mário Ferreira Conceição; Tanimoto, Matheus H.; Bastos, Jairo K.; Parreira, Renato L. T.; Orenha, Renato P.; Borges, Alexandre; Berretta, Andresa A.; et al.
Abstract: Brazilian green and red propolis stand out as commercial products for different medical applications. In this article, we report the antimicrobial activities of the hydroalcoholic extracts of green (EGP) and red (ERP) propolis, as well as guttiferone E plus xanthochymol (8) and oblongifolin B (9) from red propolis, against multidrug‐resistant bacteria (MDRB). We undertook the minimal inhibitory (MIC) and bactericidal (MBC) concentrations, inhibition of biofilm formation (MICB50 ), catalase, coagulase, DNase, lipase, and hemolysin assays, along with molecular docking simulations. ERP was more effective by displaying MIC and MBC values <100 μg mL −1 . Compounds 8 and 9 displayed the lowest MIC values (0.98 to 31.25 μg mL −1 ) against all tested Gram‐positive MDRB. They also inhibited the biofilm formation of S. aureus (ATCC 43300 and clinical isolate) and S. epidermidis (ATCC 14990 and clinical isolate), with MICB50 values between 1.56 and 6.25 μg mL −1 . The molecular docking results indicated that 8 and 9 might interact with the catalase's amino acids. Compounds 8 and 9 have great antimicrobial potential. Abstract :